Evaluation of the natural suitability of human settlements in the Western Sichuan Plateau region of China - Wang Feng; Haixia Lu; Mingshun Xiang (Scientific Reports)
Abstract The natural suitability of human settlements is greatly influenced by the distinct ecological environment and natural conditions of the plateau area, which are of great eco-environmental significance. 32 counties in China’s Western Sichuan Plateau were chosen as the study’s research subjects. The evaluation index system and weight of the natural suitability of human settlements were established, along with the obstacle degree model, using the analytical hierarchy process, the entropy method, and the integrated weight method. In order to conduct a thorough investigation into the natural suitability of human settlements in 32 counties in the Western Sichuan Plateau, ArcGIS and other software were utilized to analyze the spatial and features of tempo-spatial variations as well as establish the values and thresholds of natural suitability. This study has gathered important findings: extracting the nature reserves, the natural suitability of human settlements in the Western Sichuan Plateau ranges from 0.3898 to 0.7178, with the overall spatial decrease from the east to the west; the disaster factor and the resource factor are dominant obstacles in different suitability zones. Geographically, the eastern part of the Western Sichuan Plateau is a high plain area characterized by stable geological activities and abundant resources. In contrast, the western part is the core area of the Hengduan Mountains, marked by frequent geological activities and scarce resource availability. The natural environment solely does not define the natural suitability of human settlements in the Western Sichuan Plateau; rather, this is decided by the interaction of the social and humanistic environments with the natural environment. Thus, this study provides empirical evidence and theoretical direction for the establishment of ecological civilization in the Western Sichuan Plateau from the perspective of evaluation of natural suitability, which is crucial for promoting the area’s coordinated development and raising the standard of living for the local population.